Frequency of diagnoses in a specialized headache clinic in Buenos Aires - Nagel, Vanessa (2019)
Objective: Headache is one of the most frequent reason for consultations in neurology. The global prevalence among adults with migraine is approximately 10% with migraine, 40% for tension-type headache (TTH) and 3% for chronic daily headache. The purpose of this study is to analyze the prevalence of the diagnoses of headache and craniofacial pain among patients evaluated in a specialized headache clinic of Buenos Aires during 2017. Methods: Retrospective, descriptive study. We reviewed the electronic medical records of patients who consulted for headaches or craniofacial pain from January 1st to December 31st, 2017. Diagnoses were made according to the criteria of the International Classification of Headache Disorders (ICHD-3). Results: We reviewed 3254 electronic medical records and documented 3941 diagnoses: headache (93.03%), craniofacial pain (3.62%) and unclassifiable (3.35%). The average age was 43.14 years. 80.7% were women. Primary headaches were the most frequent diagnoses (78.54%). Migraine represented the main diagnosis (87.42%). Episodic migraine without aura was the most prevalent diagnosis (48%). Tension- type headache (TTH) was found in 8.74% of cases of primary headaches and Trigeminal autonomic cephalalgias (TACs) in 2.89%. Medication-overuse headache (MOH) represented 77.93% of the secondary headaches, and most of them also met chronic migraine criteria fulfilled criteria of chronic migraine. Primary trigeminal neuralgia represented 50% of craniofacial pain and 27% were secondary trigeminal neuralgia, mostly postherpetic or posterior to dental procedures. Regardin to the frecuency, 33.58% of the patients had chronic headache. Conclusion: In our section, migraine is the most frequent diagnosis followed by medication-overuse headache. The percentage of chronic headache is higher than the prevalence in the general population, probably because it is a tertiary center.